2004
DOI: 10.1002/cbdv.200490029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of PaclitaxelThiocolchicine Hybrids

Abstract: The bifunctional taxoid-colchicinoid hybrids 6-8 were synthesized and evaluated in assays of cytotoxicity and tubulin assembly/disassembly. All compounds showed a high degree of cytotoxicity, but, while 6 and 7 behaved as bifunctional tubulin binders not unlike an equimolecular mixture of taxol and thiocolchicine, 8 was surprisingly devoid of tubulin activity, acting on a distinct and yet to identify molecular target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3 In our recent research on the synthesis of new potential antitumor compounds, we prepared several bivalent hybrid compounds obtained by combination of podophyllotoxin, thiocolchicine, Taxol, and vinblastine derivatives. 4 In this context, we reported the synthesis of taxoid-thiocolchicine hybrids, 5 and in addition to obtaining interesting information regarding cytotoxicity of some compounds, we demonstrated that the biological activity is affected not only by the anchor position of thiocolchicine to the taxoid moiety but also by the dimension of the spacer. Therefore, the search for new multivalent molecules is a three-variable problem: two scaffolds and one linker.…”
Section: Introductionmentioning
confidence: 99%
“…3 In our recent research on the synthesis of new potential antitumor compounds, we prepared several bivalent hybrid compounds obtained by combination of podophyllotoxin, thiocolchicine, Taxol, and vinblastine derivatives. 4 In this context, we reported the synthesis of taxoid-thiocolchicine hybrids, 5 and in addition to obtaining interesting information regarding cytotoxicity of some compounds, we demonstrated that the biological activity is affected not only by the anchor position of thiocolchicine to the taxoid moiety but also by the dimension of the spacer. Therefore, the search for new multivalent molecules is a three-variable problem: two scaffolds and one linker.…”
Section: Introductionmentioning
confidence: 99%
“…To enable better and more uniform multi-drug delivery, several drug conjugation approaches have been developed to covalently link multiple therapeutic agents together prior to their administration. [5][6][7][8] These drug conjugates are expected to diminish the influence of the varying chemical properties such as molecular weight, charge, and water solubility of individual drugs on the therapeutic index of the drug combination.…”
Section: Introductionmentioning
confidence: 99%
“…Danieli and coworkers synthesized bifunctional paclitaxel and docetaxel analogs (2.2.110, 2.2.111, and 2.2.112) with conjugated thiocolchicine at the C7, C10, and C2 0 positions through succinyl linkers (Figure 8.10) [71]. These conjugates were tested in a tubulin assembly assay and evaluated for their cytotoxicities against human mammary cancer cell line MCF7.…”
Section: New Chemistry Of Paclitaxelmentioning
confidence: 99%